Implementasi Kurikulum Merdeka Belajar di Sekolah Menengah Atas (SMA) Negeri 15 Kota Semarang - Baehaqi, M Lutfi; Mubaroq, Akhmad Khusni (Innovative: Journal Of Social Science Research, 2024)
The independent curriculum is a new national education curriculum due to the unstable learning crisis due to the Covid-19 virus. The aim of this research is to describe the implementation of the independent curriculum in Senior High School 15 in Semarang City. The type of research used in this research is descriptive qualitative. The results of this research show; (1) independent curriculum learning at Senior High School 15 Semarang City is carried out starting with learning planning, namely the teacher creates teaching modules, carries out differentiated learning, and carries out formative and summative assessment activities; (2) the project to strengthen the profile of Pancasila students (P5) is carried out in two semesters, taking three project themes each year; (3) Obstacles in implementing the independent curriculum include; (a) teachers have difficulty creating teaching modules related to analysis of learning outcomes, learning objectives, and the flow of learning objectives, (b) constraints on the availability of facilities and infrastructure, especially those related to digital technology, (c) some teachers as human resources are less competent technological skills that have an impact on variations in learning models and methods.